Tổng hợp, đặc trưng cấu trúc vật liệu xCu-30Ti-SBA-15 và ứng dụng làm xúc tác phân hủy phenol trong môi trường nước - Nhượng, Vũ Văn; Nội, Nguyễn Văn; Thảo, Nguyễn Tiến (Vietnam Journal of Chemistry, 2016)
The ordered mesoporous catalytic materials xCu-30Ti-SBA-15 synthesized by sol-gel method, using Cu(NO3)2, tetra isopropyl orthotitanate (TIOT) as precursors of Cu and Ti. In the preparing materials process, Cu(NO3)2 and TIOT were calculated theoretically to obtain some photocatalysts of xCu-30Ti-SBA-15 (x and 30 as weight percent of CuO and TiO2 in materials, respectively). The pH changing on the gel forming in neutral media (pH = 7.0) was made benefit conditions for doping Cu2+ in the matrix of TiO2/SBA-15, therefor decreasing strongly band-gap energy of TiO2, in the results of transforming excitation light for synthesis materials. A set of xCu-30Ti-SBA-15 catalysts prepared was characterized by some physical techniques such as adsorption/desorption isotherm nitrogen (BET), XRD, UV-Vis DRS. Their photocatalytic activities were exhibited by percentages of transformation for phenolic in water under different  excitation light sources (UV, halogenium). Keywords. Photocatalyst, synthesis, doping, degradation, characterization.